2021
DOI: 10.3389/fmed.2021.713554
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Melasma Treatments: A Network Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Melasma is an acquired pigmentation disorder with challenges in treatment because of its refractory nature and high risk of recurrence.Objectives: This study aimed to compare the efficacy and side effects of 14 common therapies for melasma using a systematic review and network meta-analysis (NMA).Methods: The PubMed, Embase, and Cochrane Library databases were searched till December 2020 using the melasma area and severity index as a therapeutic index. A total of 59 randomized controlled trials (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 47 publications
(56 reference statements)
0
28
0
2
Order By: Relevance
“…It is also suggested that tranexamic acid can reverse melasma‐associated dermal changes, such as increased vascularity, turns this agent into an important strategy for the treatment of melasma. In addition, it is worth mentioning that tranexamic acid was recommended as first‐line therapy in a recently published systematic review 21 . However, more studies are needed to determine long‐term efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that tranexamic acid can reverse melasma‐associated dermal changes, such as increased vascularity, turns this agent into an important strategy for the treatment of melasma. In addition, it is worth mentioning that tranexamic acid was recommended as first‐line therapy in a recently published systematic review 21 . However, more studies are needed to determine long‐term efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Melasma is a refractory disorder and no single therapeutic approach has been proved to be entirely effective 11 . Intensive and prolonged photoprotection is the cornerstone in melasma management 12,14 .…”
Section: Photoprotection In Melasmamentioning
confidence: 99%
“…Patients suffering from melasma have a high‐risk of clinical relapses 11 . Prolonged use of photoprotection is highly recommended.…”
Section: Photoprotection In Melasmamentioning
confidence: 99%
“…In contrast, a recent network meta-analysis evaluated the efficacy of all currently available treatments for melasma. Chemical peels were not cited as a therapeutic option due to the paucity of high-quality randomized controlled trials [ 108 ]. Adverse effects are rare, but the primary concern is the risk of hyperpigmentation, especially in dark-skinned individuals [ 99 ].…”
Section: Introductionmentioning
confidence: 99%